2014
DOI: 10.1111/resp.12383
|View full text |Cite
|
Sign up to set email alerts
|

Can non‐invasive positive pressure ventilation prevent endotracheal intubation in acute lung injury/acute respiratory distress syndrome? A meta‐analysis

Abstract: The role of non-invasive positive pressure ventilation (NIPPV) in acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) is controversial. The aim of this study was to investigate whether NIPPV could prevent endotracheal intubation and decrease mortality rate in patients with ALI/ARDS. Randomized controlled trials (RCT) which reported endotracheal intubation and mortality rate in patients with ALI/ ARDS treated by NIPPV were identified in Pubmed, Medline, Embase, Central Cochrane Controlled Trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Early use of non-invasive ventilation (NIV) can reduce the need for intubation of mild ARDS patients [7][8][9][10][11][12]. In a few observational studies [13][14][15][16], lower rates of intubation were seen among hypoxemic patients receiving high-flow nasal cannula (HFNC) than among those receiving NIV or standard oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Early use of non-invasive ventilation (NIV) can reduce the need for intubation of mild ARDS patients [7][8][9][10][11][12]. In a few observational studies [13][14][15][16], lower rates of intubation were seen among hypoxemic patients receiving high-flow nasal cannula (HFNC) than among those receiving NIV or standard oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the meta-analysis, only three studies ( n = 89) involved patients with ARDS and the analysis also included postsurgical subjects with atelectasis. [ 10 ] In another meta-analysis involving only subjects with ARDS, it was shown that NIV avoids intubation in approximately 50% of the patients, provided the patients are judiciously chosen. [ 9 ] There is sparse data on the role of NIV from the developing world.…”
Section: Introductionmentioning
confidence: 99%
“…Although the guidelines published on behalf of the European Respiratory Society and the European Society of Intensive Care Medicine were clearly indicating the use of mechanical ventilation for severe ARDS caused by H1N1 pneumonia (13), our case report, as well as other reports and studies (14)(15)(16)(17)(18), suggest that NIPPV can be useful in well selected patients. Hence, we postulate that the absence of other organ dysfunction associated with the acute respiratory failure as well as an early improvement of the oxygenation parameters with NIPPV may warrant an attempt of noninvasive ventilation as a first line ventilatory strategy to manage patients with severe influenza A H1N1 related ARDS.…”
Section: Discussionmentioning
confidence: 60%